Evaluación del sistema de producción hortícola sobre buenas prácticas de manejo en los Valle Altos de los estados Mérida y Trujillo (Agroindustria, Sociedad y Ambiente, 2016)
Good Management Practices (BPM) is a preventive system that considers the most appropriate principles and practices in agricultural production. The objective was to evaluate the system of horticultural production on the use of BPM and sensitize farmers on the importance of implementing them. The work was carried out in the production area of the high valleys of the Andes, formed by Timotes, Miranda Municipality, Mérida State farmers and of 13 municipalities of Trujillo State-Venezuela farmers. The study was conducted in two phases, the first phase, the use of BPM of plant products was determined by direct observation and survey of producers and the Situational Analysis on the study of the strengths, weaknesses, opportunities and threats (SWOT). In the second phase, strategies for training and training on BPM developed. It is a descriptive research and data were analyzed using NCSS program using the method of independence Chi-square (χ2). Based on the results, training strategies were applied, firstly, a course of 40 hours was issued on the implementation of GMP and secondly, direct counseling and training workshops for making pickles agricultural products not complying to be marketed, handling empty agrochemical for recycling and the management and use of organic solid waste containers. Training in the use of BPM behavioral changes allowed farmers in the implementation of activities, responsibility to abide by the operating instructions for both personal hygiene and handling of products, also in ensuring the safety of products sold, better organization and registration of the work, waste management and control of factors influencing deterioration.
Keywords: Good management practices, horticultural production , training .